Critical Scaling of Diffusion Coefficients and Size of Rigid Clusters of Soft Athermal Particles Under Shear - Saitoh, Kuniyasu; Kawasaki, Takeshi (Frontiers in Physics, 2020)
We numerically investigate the self-diffusion coefficient and correlation length of the rigid clusters (i.e., the typical size of the collective motions) in sheared soft athermal particles. Here we find that the rheological flow curves on the self-diffusion coefficient are collapsed by the proximity to the jamming transition density. This feature is in common with the well-established critical scaling of flow curves on shear stress or viscosity. We furthermore reveal that the divergence of the correlation length governs the critical behavior of the diffusion coefficient, where the diffusion coefficient is proportional to the correlation length and the strain rate for a wide range of the strain rate and packing fraction Take across the jamming transition density.